1943
DOI: 10.1021/i560122a002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pH of Textile Materials

Abstract: In all previously published methods for the determination of the pH of leather, paper, and textiles, a single-extraction operation has been used on the assumption that the amount of water per unit weight of sample is relatively insignificant. The results of the present investigation, however, show that for textiles the pH of the extract solution is a function of the quantity of water used in the extraction process. An extrapolation method based on this fact is described for the determination of the pH of a fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1952
1952
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The regression equation for this relationship, in which the data of Table 11 are used, is given by y = 1.03911. + 2.192 (14) where the standard error in y is 0.13". Table 111 shows actual and assumed values of 11. for the purpose of extending the range from 40" to 23") for which values of y have been calculated from eq.…”
Section: Least Squares Analysis Of the 002 Arcmentioning
confidence: 99%
“…The regression equation for this relationship, in which the data of Table 11 are used, is given by y = 1.03911. + 2.192 (14) where the standard error in y is 0.13". Table 111 shows actual and assumed values of 11. for the purpose of extending the range from 40" to 23") for which values of y have been calculated from eq.…”
Section: Least Squares Analysis Of the 002 Arcmentioning
confidence: 99%
“…In order to establish the precision of the colorimetric method, the pH of 85. samples of cotton fiber was determined by the proposed colorimetric method and by an electrometric method adapted from the work of Wakeham and Skau [9]. This method consists of the extraction of 0.5 g. of ground cotton (20-mesh) with 3 ml.…”
Section: Precision Of the Methodsmentioning
confidence: 99%
“…Representative procedures are described by McCall et al [8], Marsh et al [7], and Hall and Elting [3]. Wakeham and Skau [9] demonstrated that the pH of an aqueous extract of cotton fabric is a function of the amount of water used for the extraction. These authors determined the pH of successive dilutions of an aqueous extract of the fabric, followed by extrapolation to zero dilution in order to define the pH in terms of the amount of water present in the fabric equilibrated to the standard atmosphere of 65% R.H. and 75 ° F. Although precise, this method does not satisfy the requirements for routine use where speed and simplicity are essential.…”
mentioning
confidence: 99%